PP41 The prevalence of drug use, including intravenous drug use, among the irish prisoner population. (31st August 2015) - Drummond, A; Kelleher, CC; Donnelly, NA; McCausland, D; Codd, M
Abstract : Background: The purpose of this study was to estimate the prevalence of drug use, including injecting drug use, among the prisoner population in the Republic of Ireland. Drug use surveys carried out by the National Advisory Committee on Drugs and Alcohol (NACDA) provide population data, but the most recent drug prevalence data on the Irish prisoner population dated from a 1999 study on Blood Borne Viruses (BBVs) in prisons. Accurate up-to-date data for service planning and policy development were required. Methods: An observational cross-sectional study was undertaken, with 824 prisoners randomly selected in proportion to the population in each prison. Data collection instruments included a self-completion questionnaire (based on European Monitoring Centre for Drugs and Drug Addiction guidelines), and oral fluid samples, which were tested for six drugs. Prevalence proportions and confidence intervals were calculated. T-tests and Chi 2 testing were used for group comparisons. Results: The response rate was 50% and the sample was representative of the full prison population. Prevalence of any drug  use for individual drugs was, not unexpectedly, higher than in the general population. Results are presented as prevalence range for individual drugs (95% CI lower and upper bounds) for: lifetime, 33% (CI: 30–36%) to 87% (CI: 85–89%); last year, 12 (CI: 10–14%) to 69% (CI: 66–71%); and last month, 2% (CI: 1–3%) to 43% (CI: 40–47%). Lifetime injecting prevalence for any drug was 26% (CI: 23–28%) and lifetime individual drug injecting rates ranged from 2 (CI: 1–2%) to 19% (CI: 17–22%). Women were significantly more likely to inject drugs than men (44% vs 24%, p < 0.01). Conclusion: The findings confirmed the need for drug treatment and harm reduction services in prisons and highlighted key risk areas and groups for specific and targeted interventions. The NACDA has published recommendations for practice, policy and research based on the results.